NMDAR Hypofunction Animal Models of Schizophrenia - Lee, Gloria; Zhou, Yi (Frontiers in Molecular Neuroscience, 2019)
The N-methyl-d-aspartate receptor (NMDAR) hypofunction hypothesis has been proposed to help understand the etiology and pathophysiology of schizophrenia. This hypothesis was based on early observations that NMDAR antagonists could induce a full range of symptoms of schizophrenia in normal human subjects. Accumulating evidence in humans and animal studies points to NMDAR hypofunctionality as a convergence point for various symptoms of schizophrenia. Here we review animal models of NMDAR hypofunction generated by pharmacological and genetic approaches, and how they relate to the pathophysiology of schizophrenia. In addition, we discuss the limitations of animal models of NMDAR hypofunction and their potential utility for therapeutic applications.